2021
DOI: 10.3390/su13169294
|View full text |Cite
|
Sign up to set email alerts
|

Circular Economy for a Sustainable Agri-Food Supply Chain: A Review for Current Trends and Future Pathways

Abstract: The current agri-food supply chain is affected by different problems such as food loss and waste generation along the supply chain, and the circular economy offers a possibility to enhance and optimize the production and consumption to seek to a sustainable paradigm. The circular economy can be a winning approach to intervene and moderate the impacts generated in the agri-food sector, proposing actions and solutions to readmit wastes and by-products in the productive chain. The aim of this work was to perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 58 publications
0
38
0
2
Order By: Relevance
“…Agriculture is well adapted to the precepts of the CE as an economic concept included in the framework of sustainable development [16][17][18]. This comprises a set of human actions dedicated to the transformation of the natural environment to provide the world's food, which depends on both the climate and the techniques implemented to make the land fertile.…”
Section: Introduction 1background and Conceptual Frameworkmentioning
confidence: 99%
“…Agriculture is well adapted to the precepts of the CE as an economic concept included in the framework of sustainable development [16][17][18]. This comprises a set of human actions dedicated to the transformation of the natural environment to provide the world's food, which depends on both the climate and the techniques implemented to make the land fertile.…”
Section: Introduction 1background and Conceptual Frameworkmentioning
confidence: 99%
“…(Figure 6). The circular economy is a new economic model, in which the old "do-it-take-away" structure wants to be replaced by a circular approach based on the "3R" principles of "reductionreuse-recycling" (Chiaraluce et al, 2021). Regarding the frequency of co-authors, depending on the country, it is observed the degree of relationship between countries and the interest given to the concept of "circularity" (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…Chiaraluce et al ( 2021 ) concluded the circular economy is a concept that represents a novel economic model, where the old linear "make-use-dispose" wants to be replaced initially by a circular approach based on the “3R” principles “reduction-reuse-recycling”.…”
Section: Circular Economy In the Sugar Industrymentioning
confidence: 99%